2007
DOI: 10.1159/000108284
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Cancer Incidence in the Population of the District Sumperk, Czech Republic

Abstract: Excess body weight was shown to be associated with risk of several types of cancer. In the Czech Republic, malignant tumors are the second leading cause of death. The aim of this study was to assess the association between the most frequent types of cancer and obesity. Methods: A case-control study was accomplished, using data from the National Cancer Registry and from a preventive oncologic checkup database. Cases were defined as persons from the studied population who developed skin, breast, colorectal, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…In another hospital-based study of 528 BCC40, women in the fourth quartile of BMI had a 34% (OR = 0.66, 95% CI: 0.35–1.22) non-significantly lower risk of BCC as compared with women in the first quartile, whereas the corresponding OR for men was 0.97 (95% CI: 0.58–1.63). In a population-based case-control study of 1276 NMSC41, obesity was associated with a non-significant increase in risk of NMSC in men (OR = 1.25, 95% CI: 0.94–1.64); conversely, a trend towards reduced risk was found in women (OR = 0.79, 95% CI: 0.62–1.01).…”
Section: Discussionmentioning
confidence: 94%
“…In another hospital-based study of 528 BCC40, women in the fourth quartile of BMI had a 34% (OR = 0.66, 95% CI: 0.35–1.22) non-significantly lower risk of BCC as compared with women in the first quartile, whereas the corresponding OR for men was 0.97 (95% CI: 0.58–1.63). In a population-based case-control study of 1276 NMSC41, obesity was associated with a non-significant increase in risk of NMSC in men (OR = 1.25, 95% CI: 0.94–1.64); conversely, a trend towards reduced risk was found in women (OR = 0.79, 95% CI: 0.62–1.01).…”
Section: Discussionmentioning
confidence: 94%
“…Studies regarding BMI and gallbladder cancer risk have been generally hampered by small numbers of outcomes and the related issues of limited statistical power and imprecise risk estimates: of the 12 prospective cohort studies on this topic in the literature (1113, 1517, 2126), six identified fewer than 100 cases (11, 12, 17, 22, 23, 25) and while most studies reported HRs above one, many studies were not statistically significant (11, 12, 15, 23, 25). With data from 567 gallbladder cancer cases, this study makes an important contribution toward confirming the association between high BMI and this rare and highly fatal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…After full-text review of the remaining 31 studies, two studies were excluded because one study did not report RR with the corresponding 95% CI and the other study did not provide sufficient data to calculate them. Thus, 14 (7,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) cohort studies and 15 (19,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61) case-control studies were included in this meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%